The real effective exchange rate in the ECCU : equilibrium and misalignment - Grenade, Kari (ECCB [Basseterre]KN, 2009)
Identifies possible causes and the extent of any misalignment in the real effective rate (REER) in the ECCU over the 1990 to 2007 period. Highlights the important roles that fiscal policies and capital inflows play in real exchange rate movements.